The Ancient aKhena People of India and Bangladesh: An Anthropological Study (Global Journal of Human-Social Science, 2018)
The ÔCoch'`Mech' and ÔTharu' were the ancient People of North-Bengal of India and Bangladesh, next important traibal people were the Khen in this territory. We are well known about the Rajbansis, Mech and coch people but we have not suffccient evidences regarding origin, migration and habitation of the Khen community. We have informations only about Khen kings and their administration, their religious and archaeological activities. History almost silent about its common people. In North-Bengal of India (Cochbihar district) and Bangladesh (District of Rangpur and Dinajpur) Khen are a remarkable shedule caste till today. We conducted a short anothropological survey on common khen people in this article. Our survey mostly based on kurigran district of Rangpur in Bangladesh.and secondary data collected from indian sources..
Keywords: khen; kamrup-kamta; ritual; proto-australoid; mongoloid